1996
DOI: 10.1523/jneurosci.16-09-03089.1996
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned and Unconditioned Stimuli Increase Frontal Cortical and Hippocampal Acetylcholine Release: Effects of Novelty, Habituation, and Fear

Abstract: Recent evidence showing that basal forebrain cholinergic neurons with projections to the frontal cortex and hippocampus are activated by behaviorally salient stimuli suggests that these neurons are involved in arousal and/or attentional processes. We sought in the present experiments to test this hypothesis by examining whether unconditioned stimuli (a tone and flashing light) that normally increase cortical nad hippocampal acetylcholine (ACh) release would fail to do so after habituation (i.e., repeated prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
193
0
4

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(212 citation statements)
references
References 61 publications
15
193
0
4
Order By: Relevance
“…However, if individuals are exposed to novelty in the absence of behaviorally relevant outcomes, as they were in our current study, the salience of novelty and the associated neurophysiological response should habituate (Sokolov 1963). As noted above, previous studies have demonstrated habituation of the HPC in prolonged exposure to a single novel environment (Wilson and Rolls 1990a,b;Acquas et al 1996;Giovannini et al 2001) or repeated exposures to the same stimuli (Henson et al 2003), as well as fear-predicting and fear-evoking stimuli (Buchel et al 1999;Fischer et al 2003). Previous research has also demonstrated that HPC responses are sensitive to experimentally instructed expectations about the value of information (Adcock et al 2006;Murty et al 2012) that should affect the salience of novelty (Wittmann et al 2007;Bunzeck et al 2010).…”
Section: Novelty Processing In the Mtlmentioning
confidence: 79%
“…However, if individuals are exposed to novelty in the absence of behaviorally relevant outcomes, as they were in our current study, the salience of novelty and the associated neurophysiological response should habituate (Sokolov 1963). As noted above, previous studies have demonstrated habituation of the HPC in prolonged exposure to a single novel environment (Wilson and Rolls 1990a,b;Acquas et al 1996;Giovannini et al 2001) or repeated exposures to the same stimuli (Henson et al 2003), as well as fear-predicting and fear-evoking stimuli (Buchel et al 1999;Fischer et al 2003). Previous research has also demonstrated that HPC responses are sensitive to experimentally instructed expectations about the value of information (Adcock et al 2006;Murty et al 2012) that should affect the salience of novelty (Wittmann et al 2007;Bunzeck et al 2010).…”
Section: Novelty Processing In the Mtlmentioning
confidence: 79%
“…Exposure to a novel environment has been shown to transiently increase cholinergic neurotransmission in the hippocampus. [35][36][37][38][39] In M2-KOs and much more in M2/M4-KOs, the increase in hippocampal acetylcholine triggered by exposure to a novel environment was more pronounced both in amplitude and duration as compared to WT mice. This enhancement in the acetylcholine response in the KO mice could be a consequence of a number of distinct phenomena, including an increase in acetylcholine synthesis or a reduction in catabolism.…”
Section: Discussionmentioning
confidence: 94%
“…Increases in cholinergic activity in the forebrain upon exposure to novelty (novel environment or other unconditioned stimulus such as light or tone) are believed to reflect primarily arousal by and/ or attention to behaviorally salient stimuli [37][38] and to a lesser extent exploratory activity or fear. 36,38 Increases in hippocampal acetylcholine release produced by unconditioned stimuli are significantly reduced by between-and within-session habituation. 38 Novelty-induced increases in acetylcholine release are transient, peaking at the first 10-15 min after presentation of the stimulus and steadily decreasing afterwards.…”
Section: Discussionmentioning
confidence: 99%
“…This type of conditioning has been demonstrated across the phylogenetic scale from gastropod molluscs (Hawkins et al 1983) to humans (Hodes et al 1985), and the synaptic changes involved (Kandel & Schwartz 1982) represent one of the simplest forms of value-dependent neural plasticity (Friston et al 1994). In mammals, this plasticity of neural response appears to involve neuromodulatory cholinergic projections, predominantly from the nucleus basalis of Meynert in the basal forebrain (Pirch et al 1992 ;Hars et al 1993 ;Acquas et al 1996).…”
Section: Introductionmentioning
confidence: 98%